PRELIMINARY FRAMEWORK FOR A DIGITAL MARKETING SUPPORT SCHEME FOR ASNAF ENTREPRENEURS BY ZAKAT INSTITUTIONS IN MALAYSIA - Fathullah Asni; Wan Azani Mustafa; Khalilullah Amin Ahmad; Nor Izham Subri, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Asnaf entrepreneurship has been recognized as one of the key strategies for poverty alleviation and economic empowerment of low-income groups. In Malaysia, various productive zakat programs have been implemented by state zakat institutions to help asnaf increase their income through entrepreneurial activities. However, most of these programs have primarily focused on providing capital and basic equipment without incorporating significant marketing strategies. In reality, many asnaf entrepreneurs face challenges in penetrating wider markets due to a lack of knowledge and skills in digital marketing, compounded by the high cost of advertising. This lack of digital marketing capability limits their businesses to local customers only, making it difficult for them to grow in the increasingly competitive digital economy. This article aims to propose a preliminary framework for a Digital Marketing Support Scheme for asnaf entrepreneurs, to be implemented by zakat institutions. The scheme is designed to assist potential asnaf entrepreneurs in increasing their sales through engagement in digital platforms. A conceptual approach is employed, building arguments based on existing literature and current needs analysis. The proposed implementation model consists of three main phases: identification and basic training, subsidized support and performance monitoring, and recognition and self-empowerment. The core components of the scheme include digital advertising subsidies, structured training, continuous mentoring, and the development of an asnaf digital entrepreneurship community. The conceptual analysis suggests that the implementation of this scheme has the potential to enhance the effectiveness of productive zakat programs by opening wider market opportunities for asnaf entrepreneurs. The scheme also aligns with the government’s policy of strengthening the digital economy and micro-entrepreneurship. This article recommends that zakat institutions conduct pilot studies to assess the effectiveness of the proposed model before scaling it up as a national initiative.